ЗАЩИТА ПРАВ НАЦИОНАЛЬНЫХ МЕНЬШИНСТВ В РЕСПУБЛИКЕ МОЛДОВА: ОСНОВНЫЕ ЗАКОНОДАТЕЛЬНЫЕ АКТЫ - Боршевский, Андрей (SUPREMANCE OF LAW, 2016)
This article describes the national legislation to protect the rights of ethnic minorities. All human beings are equal before the law and are entitled to equal protection of the law against any discrimination and against any incitement to discrimination. Discrimination between human beings on the grounds of race, colour or ethnic origin is an obstacle to friendly and peaceful relations among nations and is capable of disturbing peace and security among peoples and the harmony of persons living side by side even within one and the same State, the existence of racial barriers is repugnant to the ideals of any human society. United Nations Declaration on the Elimination of All Forms of Racial Discrimination of 20 November 1963 (General Assembly resolution 1904 (XVIII)) solemnly affirms the necessity of speedily eliminating racial discrimination throughout the world in all its forms and manifestations and of securing understanding of and respect for the dignity of the human person.
Keywords: ethnic minorities; rights of ethnic minorities; NGO; national legislation